Evaluation of coagulation parameters: Coronavirus disease 2019 (COVID-19) between survivors and nonsurvivors - Ozdin,Mehmet (2021)
SUMMARY OBJECTIVE: This study aims to investigate and compare the coagulation parameters of coronavirus disease 2019 (COVID-19) patients with mortal and nonmortal conditions. METHODS: In this study, 511 patients diagnosed with COVID-19 were included. Information about 31 deceased and 480 recovered COVID-19 patients was obtained from the hospital information management system and analyzed retrospectively. Whether there was a correlation between coagulation parameters between the mortal and nonmortal patients was analyzed. Descriptive analyses on general characteristics of the study population were performed. Visual (probability plots and histograms) and analytical methods (Kolmogorov–Smirnov and Shapiro–Wilk test) were used to test the normal distribution. Analyses were performed using the SPSS statistical software package. RESULTS: Out of 511 patients, 219 (42.9%) were females and 292 (57.1%) were males. There was no statistically significant difference between males and females in terms of mortality (p=0.521). In total, the median age was 67 (22). The median age was 74 (13) in the nonsurvivor group and 67 (22) in the survivor group, and the difference was statistically significant (p=0.007). The D-dimer, prothrombin time, international normalized ratio, neutrophil, and lymphocyte median age values with p-values, in the recovered and deceased patient groups were: 1070 (2129), 1990 (7513) μg FEU/L, p=0.005; 12.6 (2.10), 13.3 (2.1), p=0.014; 1.17 (0.21), 1.22 (0.19), p=0.028; 5.51 (6.15), 8.54 (7.05), p=0.001; and 0.99 (0.96), 0.64 (0.84), p=0.037, respectively, with statistically significant differences. CONCLUSIONS: As a result of this study, D-dimer, prothrombin time, and international normalized ratio increase were found to be associated with mortality. These parameters need to be closely monitored during the patient follow-up.